Avulsion fragmentation of the tibial tuberosity apophysis and associated patellar tendon enthesopathy in a skeletally immature dog - Brown, G. W.; Kalff, S.; Parry, A.; Whitehead, M.; McKee, W. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
A 9.5-month-old, female entire, 31.3 kg crossbred dog was presented with a 12 week history of moderate weight-bearing right pelvic limb lameness. Radiographic, computed tomographic, and ultrasonographic imaging revealed progressive avulsion fragmentation of the right tibial tuberosity apophysis and a patellar tendon insertional enthesopathy without physeal involvement. Conservative management was successful in achieving a good clinical outcome. A progressive avulsion of the contralateral proximal tibial physes that occurred concurrently resulted in development of an excessive tibial plateau slope angle. The additional development of a moderate left distal femoral varus deformity was surgically corrected. This is the first report of a progressive, traction injury to the tibial tuberosity apophysis in a dog that appears clinically and radiographically very similar to Osgood-Schlatter disease in humans.
Keywords: Tibial tuberosity; Osgood-Schlatter disease; apophysis